Causes of the economic crisis in Southeast Asia - Bieliūnaitė, Živilė (Politologija, 1999)
The essay examines internal (institutional) as well as external causes of the economic crisis in Southeast Asia (South Korea, Indonesia, Malaysia, Thailand, and the Philippines) in 1997–98. It is argued in the essay that the crisis in the above-mentioned countries resulted from the coincidence of their weak/weakened institutional structures and negative external impacts, i.e., incapacity of national governments to control global capital flows, "contagion" originating from countries’ economic interdependence, and improper behavior of external actors, such as the IMF. The analysis of the institutional weakness/strength is based on statist (developmental state) theoretical assumptions. Scholars have already for a long time used developmental theory assumptions to explain the East/Southeast Asian economic "miracle." According to the developmental state theories, two conditions are necessary to promote successful economic development: first, autonomous bureaucratic apparatuses, and second, specific (symbiotic) "partnership" between state elites and capital owners (i.e., embeddedness). The institutional preconditions in South Korea and Indonesia were "appropriate" for successful economic development during 1965–80. However, they have gradually degenerated into corrupt corporate structures producing economic inefficiency. True, weak institutional structures alone do not cause any sudden and wide-scale breakdown of economic systems. In South Korea and Indonesia, institutional weakness led to the accumulation of the "critical mass" of the crisis, but the crisis sprang up only when the domestic non-productiveness was additionally triggered by negative external factors, i.e., "contagion" leading to currency devaluation. Institutional structures in Malaysia, Thailand, and the Philippines, according to "developmental state" theoretical assumptions, have never been "appropriate" for successful state-led economic development. The reasons why the state itself has been unable to carry out successful interventionist economic policy vary from country to country—e.g., ethnic divides in Malaysia, steadily limited mass support for the governments in Thailand, lacking traditions of cooperation between state elite and social groups in the Philippines, etc. As the governments in Malaysia, Thailand, and the Philippines were disposed to perform less interventionist economic policy and promote economic growth, they relied more on foreign investors. Correspondingly, the external factors ("non-governable" speculative capital flows, etc.) were of deterministic importance in provoking the onset of economic crisis in these countries. The IMF "stabilization" policy discussed in the essay was one of the external factors that deepened the crisis in Thailand, Indonesia, and South Korea in 1998. It is argued that IMF conditionality was inadequate in the Southeast Asian macroeconomic context and led to lasting economic stagnancy.